Isolated Abducens Nerve Avulsion at Pontomedullary Sulcus following Trivial Head Injury - Maila, Sharath Kumar; Sunnadkal, Rajani Somappa (Indian Journal of Neurosurgery, 2015)
Abducens nerve palsy is commonly seen in neurosurgical practice. However, the abducens nerve palsy secondary to an avulsion injury is extremely rare. The patients present clinically with diplopia and show lateral rectus palsy. Here, the authors present a case report of such an unusual condition following a trivial trauma presenting clinically with left lateral rectus palsy. The course of the nerve and a possible mechanism of such an injury and management are discussed. To the authors knowledge, there is no reported case of an isolated unilateral avulsion injury of the abducens nerve following trauma before this report.
Keywords: abducens nerve; sixth cranial nerve palsy; avulsion injury; lateral rectus palsy